An International Prospective Cohort Study of HIV and Zika in Infants and Pregnancy (HIV ZIP): Study Protocol - Ann Aschengrau; Marisa M. Mussi-Pinhata; John Moye; Nahida Chakhtoura; Kunjal Patel; Paige L. Williams; Brad Karalius; Patricia A. Garvie; Dina Monte; Frances Whalen; Jill Lebov; George R. Seage (Frontiers Media S.A., 2021)
Zika virus (ZIKV) infection may adversely affect pregnancies of women living with HIV (WLHIV). Because no study to date has focused on maternal and child effects of HIV and ZIKV co-infection in pregnant women, we undertook the International Prospective Cohort Study of HIV and Zika in Infants and Pregnancy (HIV ZIP). The aims of this two-phase study of pregnant women and their infants are to compare the incidence of ZIKV infection among pregnant women with and without HIV infection and to determine the risk of adverse maternal and child outcomes associated with ZIKV/HIV co-infection at clinical sites in Brazil, Puerto Rico, and the continental United States. Phase I was designed to enroll pregnant women/infant pairs who were: (1) infected with HIV only, (2) infected with ZIKV only, (3) infected with HIV and ZIKV, and (4) not infected with either HIV or ZIKV. A key goal of this phase was to assess the feasibility of enrolling 200 women/infant pairs within a year, with a target of 150 WLHIV, 50 HIV-uninfected women, and a minimum of 20 who were co-infected with HIV and ZIKV. If the feasibility of Phase I proved successful, Phase II would enroll up to 1,800 additional pregnant women/infant pairs to the same four groups. Enrolled women in both phases were to be followed throughout their pregnancy and up to 6 weeks post-partum. Infants were also to be followed for 1 year after birth. To date, Phase 1 data collection and follow-up have been completed. Delineation of possible harmful effects of HIV/ZIKV co-infection will allow the formulation of standard-of-care recommendations to minimize adverse effects but enable the continuation of preventive HIV therapy. Furthermore, while the prospective HIV ZIP study was developed before the COVID pandemic, it is especially relevant today since it can be easily adapted to provide critically important information on the impact of COVID-19 infection or other still unrecognized new agents among pregnant women and their offspring worldwide.